Fibrinolytic therapy in very elderly patient with pulmonary embolism: Age is not a contraindication - KASAPOĞLU, UMUT SABRİ; KARAKURT, SAİT (My University, 2023)
Introduction: Pulmonary embolism (PE) is a life threatening medical condition, and 34% of the patients died suddenly or within a few hours of the acute event before therapy could be initiated. Lysis of clot can be achieved faster with fibrinolytic therapy in high risk PE patients. But fibrinolytic therapy is administered with great caution in elderly patients because the risk of complications is thought to be higher than in non-elderly patients. We aimed to describe clinical and treatment characteristics of the very elderly PE patient that received with fibrinolytic therapy. Case: An 83-year-old female patient with history of alzheimer disease admitted to the emergency department with new onset shortness of breath, chest pain and an episode of syncope. On presentation to the emergency room, she was hemodynamically unstable, heart rate was 105 beats/min, blood pressure was 80/50 mmHg, respiratory rate was 25 breaths/minute, and saturation was 85% on room air. She has been admitted to the intensive care unit due to shock and acute respiratory failure. A bedside ECHO was performed to diagnose the differential diagnosis of cause of shock in the patient, and right ventricular dilation and dysfunction were detected. After hemodynamic stabilization of the patient, a CTPA was performed. The CTPA revealed multiple scattered thrombi in both pulmonary artery branches (Figure 1). Fibrinolytic therapy with recombinant tissue plasminogen activator was administered. Patient clinical condition and laboratory findings were significantly improved, and was discharged was discharged from the intensive care unit on the fifth day of admission and transferred to the ward. Discussion: Clinical studies have shown that in patients with PE who received fibrinolytic therapy, the rates of death and illness associated with this condition are similar between older and younger age groups. Thus, age should not be regarded as a contraindication to fibrinolytic therapy in patient with PE.
Keywords: Fibrinolytic treatment; elderly; pulmonary embolism; high risk